2022
DOI: 10.3389/fsurg.2022.940391
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic antibiotics may not be necessary for transoral endoscopic thyroidectomy

Abstract: BackgroundWith the recent advances in thyroid cancer surgery techniques and the increasing number of patients concerned about cosmetics, the use of transoral endoscopic thyroidectomy is increasing globally. The aim of this study was to determine whether transoral endoscopic thyroidectomy is truly a clean-contaminated surgery.MethodsFrom September 2016 to April 2018, 20 patients with thyroid cancer underwent transoral endoscopic thyroidectomy performed by a single surgeon at Gangnam Severance Hospital. Before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Their study also found that the use of prophylactic antibiotics and enoral mucosal disinfection before surgery may be effective in reducing the risk of infection [82]. However, another study reached a different conclusion, showing that the use of prophylactic antibiotics may not be necessary in TOETVA due to the normal flora in the oral cavity acting as a barrier against potential pathogens [83]. This study also found that this procedure may not require prophy-lactic antibiotics because there is no invasion of non-resident bacterial flora [83].…”
Section: Natural Orifice Surgerymentioning
confidence: 98%
See 1 more Smart Citation
“…Their study also found that the use of prophylactic antibiotics and enoral mucosal disinfection before surgery may be effective in reducing the risk of infection [82]. However, another study reached a different conclusion, showing that the use of prophylactic antibiotics may not be necessary in TOETVA due to the normal flora in the oral cavity acting as a barrier against potential pathogens [83]. This study also found that this procedure may not require prophy-lactic antibiotics because there is no invasion of non-resident bacterial flora [83].…”
Section: Natural Orifice Surgerymentioning
confidence: 98%
“…However, another study reached a different conclusion, showing that the use of prophylactic antibiotics may not be necessary in TOETVA due to the normal flora in the oral cavity acting as a barrier against potential pathogens [83]. This study also found that this procedure may not require prophy-lactic antibiotics because there is no invasion of non-resident bacterial flora [83]. However, the study had a small sample size and was retrospective in design, so further studies are needed to confirm these findings.…”
Section: Natural Orifice Surgerymentioning
confidence: 99%